Application of Partial Connection Number and Subtraction Set Pair Potential in Evaluation of Development Trend of Water Environment Bearing State (International Journal of Scientific Research and Management (IJSRM), 2022)
Aiming at the uncertainty between the evaluation samples and the evaluation standards in the evaluation of water environment carrying capacity, a five-element connection coefficient evaluation model for water environment carrying capacity based on the set pair analysis theory is constructed, and the partial connection coefficient method and the subtractive set pair potential method are used. The development trend of the water environment carrying state was analyzed, and the method was used in the dynamic evaluation of the water environment carrying capacity in HJ City. The results show that the water environment carrying capacity of HJ city in 2015-2021 is between grades IV and III, and the water environment carrying capacity is poor, but the overall potential is developing from partial antipodal to homogeneous, showing a development trend for the better. According to the comprehensive index evaluation results, targeted suggestions for improving the water environment carrying capacity are put forward. From the analysis, it can be seen that the above dynamic evaluation and analysis results are reasonable and reliable, and the method is intuitive and simple, which can provide a reference basis for the improvement of regional water environment quality.